2010
DOI: 10.1016/s1470-2045(09)70306-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy for locally advanced head and neck cancer: 10-year follow-up of the UK Head and Neck (UKHAN1) trial

Abstract: SummaryBackgroundBetween 1990 and 2000, we examined the effect of timing of non-platinum chemotherapy when combined with radiotherapy. We aimed to determine whether giving chemotherapy concurrently with radiotherapy or as maintenance therapy, or both, affected clinical outcome. Here we report survival and recurrence after 10 years of follow-up.MethodsBetween Jan 15, 1990, and June 20, 2000, 966 patients were recruited from 34 centres in the UK and two centres from Malta and Turkey. Patients with locally advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 17 publications
4
68
1
Order By: Relevance
“…Xerostomia as a result of radiotherapy is a significant burden on QOL 22 and represented the most common chemotherapy related toxicity after six months in a large study by Tobias et al 23 Taste was worst affected in our chemoradiotherapy group but this did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 56%
“…Xerostomia as a result of radiotherapy is a significant burden on QOL 22 and represented the most common chemotherapy related toxicity after six months in a large study by Tobias et al 23 Taste was worst affected in our chemoradiotherapy group but this did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 56%
“…11 IMRT is now used more widely because it is thought to reduce the risk, 12 but we know of no convincing evidence to support this.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that BLM was associated with other cytotoxic reagents for the treatment of testis cancer and Hodgkin disease, and the particularity of these two diseases is the high cure rate obtained by chemotherapy [5,6]. BLM also shows anti-tumor activity in other malignancies, including head and neck, cervix, and vulva cancers [7][8][9][10][11][12]. However, the effects of BLM on proliferation, cell cycle, apoptosis, migration and invasion, and the potential mechanism of BLM in gastric cancer cells have not been reported.…”
Section: Introductionmentioning
confidence: 99%